I’dâd al-Fîdiyu at-Ta’lîmiy li Ta’lîm Mahârah al-Kalâm fî Kitâb alArabiyyah baina Yaday Awlâdina - Chamidah, Dewi; CM, Taqyuddin ibnu syafi'i; Faisol, Faisol (Jurnal Internasional Pendidikan Bahasa Arab, 2024)
Video is one of the best means of teaching languages in this technological age. There is a lot of research that has been successful in developing the process of teaching Arabic through these videos. This research aims to describe how to prepare the educational video in the Arabic book in the hands of our children using the Canva website. And measure its suitability to teach the skill of speech. The researcher uses the design research approach in three steps: analyzing practical problems, developing solutions, and testing and improvements. We find through the video validity level of the Learning Materials Expert Test is 91%, and from the Technology Expert 87%, until the two results combine at 89%. And from the results of student questionnaires 89.89%. So we can say that this video is very decent to use in the educational environment.